Adalimumab for long-term treatment of psoriatic arthritis: 2-year data from the Adalimumab Effectiveness in Psoriatic Arthritis Trial (ADEPT). Issue 5 (6th August 2008) - Mease, P J; Ory, P; Sharp, J T; Ritchlin, C T; Van den Bosch, F; Wellborne, F; Birbara, C; Thomson, G T D; Perdok, R J; Medich, J; Wong, R L; Gladman, D D
Abstract : Objective: To evaluate the long-term effectiveness and tolerability of adalimumab in the treatment of psoriatic arthritis (PsA). Methods: Patients with PsA who completed a 24-week, double-blind study of adalimumab versus placebo were eligible to enroll in an open-label extension study and receive adalimumab 40 mg subcutaneously every other week for up to an additional 120 weeks. At the time of this analysis, available efficacy evaluations throughout 2 years of treatment (n  =  245) included American College of Rheumatology (ACR) 20%, 50% and 70% improvement scores, measures of joint disease and skin disease, disability and quality of life; modified total Sharp scores (mTSS) were available for 2.75 years of treatment for patients who received adalimumab in the 24-week study. Results: After 24 weeks of double-blind treatment, the mean change in mTSS was −0.2 for the adalimumab group (N  =  144) and 1.0 for the placebo group (N  =  152; p<0.001), and outcomes for all individual ACR component variables were significantly improved in adalimumab compared with placebo-treated patients. Compared with 24-week responses, inhibition of radiographic progression and improvements in joint disease were maintained in most patients during long-term, open-label adalimumab treatment. Also, improvements in skin disease were maintained, with >20% of patients achieving the strict criterion of psoriasis area and severity index 100. The nature and frequency of adverse events during long-term adalimumab treatment were consistent with the safety profile during short-term treatment. Conclusions: The clinical and radiographic efficacy of adalimumab demonstrated during short-term treatment was sustained during long-term treatment. Adalimumab has a favourable risk–benefit profile in patients with PsA. Trial registration number: NCT00195689.